2020
DOI: 10.1097/inf.0000000000002914
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent Interactions Among Clinical Characteristics, Viral Loads and Disease Severity in Young Children With Respiratory Syncytial Virus Infection

Abstract: Background: Age-dependent differences in clinical presentation and viral loads in infants and young children with respiratory syncytial virus (RSV) infection, and their correlation with disease severity are poorly defined. Methods: Previously healthy children <2 years old with mild (outpatients) and severe (inpatients) RSV infection were enrolled and viral loads measured by polymerase chain reaction in nasopharyngeal swabs. Patients were stratified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
12
2
Order By: Relevance
“…Regarding the clinical diagnosis, HBoV1 single detection in RS was linked to bronchiolitis and pneumonia (Tables 2 and 3), in agreement with previously published reports ⁠ [12, 52–55]⁠. In general, frequent clinical signs and symptoms of HBoV1 infection are similar to those associated with other common respiratory viral agents [56, 57]⁠, with cough and rhinitis as remarkable features of single HBoV1 infection ().…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the clinical diagnosis, HBoV1 single detection in RS was linked to bronchiolitis and pneumonia (Tables 2 and 3), in agreement with previously published reports ⁠ [12, 52–55]⁠. In general, frequent clinical signs and symptoms of HBoV1 infection are similar to those associated with other common respiratory viral agents [56, 57]⁠, with cough and rhinitis as remarkable features of single HBoV1 infection ().…”
Section: Discussionsupporting
confidence: 88%
“…Despite the limitations of the small sample size and single‐center experience, we found that the rates of RSV/SARS‐CoV‐2 coinfections were lower than that expected based on previous experience with endemic coronaviruses, which typically range from 8% to 12%, 5 suggesting the possibility of viral interference. In fact, before the COVID‐19 pandemic endemic coronaviruses have been the second most common codetected viruses in infants with RSV‐LRTI.…”
Section: Figurecontrasting
confidence: 70%
“…Two children had underlying comorbidities, a 9-monthold born at 29 weeks of gestation and with no additional risk factors (in Group 2), and a healthy 3-month-old born at 36 weeks of gestation (in Group 3). We found that 62.5% of children in Despite the limitations of the small sample size and single-center experience, we found that the rates of RSV/SARS-CoV-2 coinfections were lower than that expected based on previous experience with endemic coronaviruses, which typically range from 8% to 12%, 5 suggesting the possibility of viral interference. In fact, before the COVID-19 pandemic endemic coronaviruses have been the second most common codetected viruses in infants with RSV-LRTI.…”
contrasting
confidence: 61%
“…In addition, our data also demonstrated that there was no significant difference in clinical types among age groups. In general, unlike other respiratory viral infections (such as respiratory syncytial virus) ( 19 ), the SARS-COV-2 infection in children has no age-dependent distribution. Interestingly, a previous study demonstrated that children aged 6 through 15 years had a longer persistence of viral genome in nasopharyngeal samples ( 20 ).…”
Section: Discussionmentioning
confidence: 98%